Strategi Pendidikan Inklusif Berbasis Pemikiran Al-Ghazali: Suatu Tinjauan Literatur - Rendy Amora Jofipasi; Jon Efendi; Robbi Asri (Universitas Lancang Kuning, 2023)
This article discusses an inclusive education strategy based on Al-Ghazali's thinking as an effort to improve access and quality of education for children with special needs. Al-Ghazali's thinking, a prominent Islamic philosopher, provides a relevant ethical and moral foundation for guiding inclusive education. This strategy involves the application of tarbiyah values (character formation) and the concept of equality in learning. Al-Ghazali’s teachings explore how education can be tailored to meet the diverse needs of students. Al Ghazali's thinking about equality and social responsibility also plays an important role in the implementation of inclusive education for students with special needs. The research aim of this article is to reveal inclusive education strategies in the development of curricula based on the character and ethical values of different learning styles, student needs, and support for students in inclusive settings. By embracing the Al-Ghazali perspective, inclusive education can be a means of building a more inclusive society that respects diversity. The results of the research show that an inclusive education strategy based on Al-Ghazali's thinking can provide a solid philosophical and ethical foundation for achieving meaningful and sustainable inclusive education. Thus, this effort not only tries to understand Al-Ghazali's educational philosophy, but also to apply it in a modern context to advance inclusive education that recognizes and respects individual diversity within society.